Inverse gas chromatography analysis of spruce fibers with different lignin content - Peterlin, Simona (2010)
Unbleached TMP spruce fibers were stepwise delignified by KMnO4/H2SO4 and five partly delignified samples were obtained. Fibers were characterized in terms of carboxylic groups, lignin and hemicelluloses content. IGC measurements were performed in the untreated fibers and in the five delignified fiber samples, as well as in microcrystalline cellulose (MCC). Different parameters, such as the dispersive component of the surface free energy (cds), the free energy and the enthalpy of adsorption with nonpolar probes (DGda and DHda , respectively), as well as the specific interactions with polar probes, quantified by the free energy and the enthalpy of adsorption (DGs a and DHsa , respectively), were determined. The values of cds and DGda are for all samples lower than for pure cellulose and vary slightly with the amount of lignin. For small contents of lignin, the values of DGs a of the acidic probes decrease with the delignification whereas those of the basic probes increase, pointing to a rather acidic character of the fibers due to the increase of the relative amount of the carbohydrates. The values for MCC corroborate these findings. Despite the substantial variation in the carboxylic group content during delignification, no clear tendencies were detected regarding the affinity with the basic probes.